Quantifying excess mortality during the COVID-19 pandemic in 2020 in The Gambia: a time-series analysis of three health and demographic surveillance systems. (March 2023) - Mohammed, Nuredin I.; Mackenzie, Grant; Ezeani, Esu; Sidibeh, Mamadi; Jammeh, Lamin; Sarwar, Golam; Saine, Aji Kumba Folawiyo; Sonko, Bakary; Gomez, Pierre; Dondeh, Bai Lamin; Hossain, M. Jahangir; Jasseh, Momodou; et al.
HIGHLIGHTS: Estimating pandemic-related excess mortality in Sub-Saharan Africa entails additional challenges. These include a lack of reliable death registration systems and limited testing capacity in most of Sub-Saharan Africa. Time-series analysis of local health and demographic surveillance systems data may provide an opportunity to address the gap in information during pandemics. Using The Gambia health and demographic surveillance systems, we show that there was little evidence of overall excess mortality in 2020. However, excess mortality may have occurred among vulnerable age groups. ABSTRACT: Objectives: Estimates for COVID-19-related excess mortality for African populations using local data are needed to design and implement effective control policies. Methods: We applied time-series analysis using data from three health and demographic surveillance systems in The Gambia (Basse, Farafenni, and Keneba) to examine pandemic-related excess mortality during 2020, when the first SARS-CoV-2 wave was observed, compared to the pre-pandemic period (2016-2019). Results: Across the three sites, average mortality during the pre-pandemic period and the total deaths during 2020 were 1512 and 1634, respectively (Basse: 1099 vs 1179, Farafenni: 316 vs 351, Keneba: 98 vs 104). The overall annual crude mortality rates per 100, 000 (95% CI) were 589 (559, 619) and 599 (571, 629) for the pre-pandemic and 2020 periods, respectively. The adjusted excess mortality rate was 8.8 (-34.3, 67.6) per 100, 000 person-month with the adjusted rate ratio (aRR) = 1.01 (0.94, 1.11). The age-stratified analysis showed excess mortality in Basse for infants (aRR = 1.22 [1.04, 1.46]) and in Farafenni for the 65+ years age group (aRR = 1.19 [1, 1.44]). Conclusion: We did not find significant excess overall mortality in 2020 in The Gambia. However, some age groups may have been at risk of excess death. Public health response in countries with weak health systems needs to consider vulnerable age groups and the potential for collateral damage. Graphical abstract: Image, graphical abstract